PENGARUH PEMBERIAN BOLU KUKUS DAUN KATUK TERHADAP PRODUKSI ASI DI WILAYAH KERJA RUMAH SAKIT GRANDMED LUBUK PAKAM - Raini Panjaitan; Reno Irwanto; Nadia Husna; Andreais Boffil Cholilulloh (JURNAL KESMAS DAN GIZI (JKG), 2020)
Katuk leaves can increase breast milk production because it’s have polyhenols and steroids were instrumental in prolactin reflex to produce breast milk, and can stimulate the hormone oxytocin to stimulate spending and flow of breast milk. Breast milk production and expenditure is influenced by two hormones, prolactin and oxytocin.This studi aims to determine the effect of giving katuk leaves steamed sponge cake for breast milk production in Grandmed Hospital Lubuk Pakam. This research method is quasi experiment with pre and posttest design. The population in this study is breastfeeding mothers of infants 0-6 months in Grandmed Hospital Lubuk Pakam. The sample is 30 people consisting of 15 control and 15 treatment group. In the treatment group was given intervention katuk leaves steamed sponge cake as much as 100 grams (2pieces) every day for 30 days. From the result of this research average frequency of breastfeeding in the control group as 8.07 time and the treatment group times as much as 10.40. While the average duration of breastfeeding in the control group as much as 6.80 minutes and 9.74 minutes in the treatment group. The result of the analysis with T-test was obtained p Value 0,000, it can concluded that there is the effect of giving katuk leaves steamed sponge cake katuk for breast milk production.